Analisis Faktor Penyebab Kontaminasi Material Slurry pada PT Cataler Indonesia dengan Metode FMEA - Rahmadin, Ahmad Arya; Putra, Fibi Eko; Andriyansyah, Agus (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Contamination of slurry material in the production process can reduce product quality and increase the risk of defects. This study aims to identify the causes of contamination and determine improvement priorities using Failure Mode and Effect Analysis (FMEA), Fishbone Diagram, and 5W+1H analysis. Data were collected through field observations, interviews with production leaders, and company documentation. The results show that the main causes of contamination come from human, method, machine, material, and environmental factors. Based on FMEA analysis, the highest Risk Priority Number (RPN) is found in equipment cleanliness and inconsistent work procedures. Improvement recommendations focus on enhancing standard operating procedures (SOP), operator training, and production environment control. The implementation of improvements is expected to significantly reduce contamination risks.